AN OVERVIEW OF THE ACHIEVEMENT OF THE NUTRITION PROGRAM IN THE POSYANDU OF THE PASIE RAYA HEALTH CENTER WORKING AREA - Nurdin, Ambia; Malena, Malena (Transpublika Publisher, 2023)
This research aims to evaluate the achievements of the Nutrition program in the Posyandu within the Pasie Raya Puskesmas working area. The program is implemented through guidance and counseling provided during Posyandu activities in the villages under the Pasie Raya Puskesmas jurisdiction. The study was conducted from September 2023 to January 2024 across all villages in the Pasie Raya sub-district/Pasie Raya Health Center area. The target population includes all Posyandu participants in the 14 villages of the Pasie Raya sub-district/Pasie Raya Community Health Center area, totaling 6,006 toddlers during the period from January to November 2023. The research employs a descriptive qualitative method, utilizing documentation data collected from the Pasie Raya Community Health Center. During the January-November 2023 period, 5,684 toddlers were weighed at the Posyandu within the Pasie Raya Community Health Center working area, out of the total 6,006 toddlers. This indicates that 358 toddlers did not undergo weighing during Posyandu sessions. Based on this data comparison, it can be concluded that the Nutrition coaching and counseling program at the Posyandu within the Pasie Raya Community Health Center area in Pasie Raya District, Aceh Jaya Regency, achieved a success rate of 95%, meeting the specified objectives.